Embracing youth volunteerism through digital literacy for a sustainable future - Zubeyr, Elyas; Kunasegaran, Mageswari; Kunjiapu, Shamuni (Human Resources Management Academic Research Society (HRMARS), 2024)
In an increasingly digitalised world, youth engagement in volunteer activities is crucial for fostering sustainable cities and communities. This study aims to offer comprehensive insight into the challenges and opportunities of cultivating a volunteer-oriented youth in the era of the Industrial Revolution 5.0. The results of the study will be used to understand youth perceptions of volunteer involvement and integration as virtually connected to attract and sustain many volunteers. It will contribute to Sustainable Development Growth 11 and 4. A narrative study design was selected to conduct this study. Observational notes, texts, and documents were used to gather the data from online databases, which was then subjected to content analysis. The findings suggest that an integrated system that nurtures volunteer-oriented youth can significantly increase the attraction, commitment, and longevity of volunteers, enabling young individuals to participate in volunteerism and community service, irrespective of their geographical location or circumstance.